Progress in separation and purification. - Perry, Edmond S. (New York, Interscience Publishers., 1968)
Contents: v. 1-2, Modern separation methods of macro molecules and particles.
Editor: v. 1- E. S. Perry.
Includes bibliographical references and index.
Also issued online.
Superseded by: Separation and purification methods (Software ed.), and by: Separation and purification methods (Hardcover ed.).
SERBIB/SERLOC merged record
Keywords: Separation (Technology); Chemical Engineering -- Periodicals; Chemistry, Analytical -- Periodicals